Globalization, embedded realism, and path dependence: the other immigrants to Europe - Hansen, Randall (2002)
Long confined to historians and sociologists, the study of immigration has garnered increased interest among political scientists. Two dominant schools - the globalization and embedded realist theses - have attempted to account for the gap between restrictionist intentions of governments and continuing immigation (the gap hypothesis). The globalization thesis argues that international norms and institutions limit governments' ability to control migration; the embeded realist thesis counters that limits on state autonomy are domestic. This article argues that although the embedded realist thesis is on stronger conceptual ground, both fail to account for two central categories of immigrants to Europe: colonial immigrants to France and Britain and asylum seekers to Germany. Drawing on historical institutionalist work, this article employs a path-dependent analysis to account for these categories. Against their own wishes, government found themselves accepting larger migrations and naturalizations because of the path-dependent effects of their own citizenship and constitutional regimes. - Reproduced.
Keywords: Globalization; Immigrants